Effect of the gut microbiome and inflammation-related proteins on oral leukoplakia: a Mendelian randomization study and mediation analysis - Da, Junlong; Ren, Yinting; Liu, Shiwei; Wang, Nanyan; Wang, Lei; Fu, Zhifeng; Liang, Yongtang; Pan, Yu (Frontiers in Oncology, 2024)
BackgroundOral leukoplakia (OL) is the most common potentially malignant disease of the oral cavity. In recent years, studies have identified a correlation between the gut microbiota (GM) and oral cancer, in addition, inflammation-related proteins have been reported to play an important role in the development of OL. However, the causal relationship between gut microbiota and OL, as well as whether cytokines play a mediating role, remain unclear.MethodsIn this Mendelian randomization (MR) study, the genome-wide association studies (GWAS) (n=18340) of the MiBioGen consortium microbiome was used as exposure data. Genetic variation data related to OL were extracted from the Finngen R9 project (513 cases of OL and 411668 controls). The 91 inflammation-related proteins obtained in the literature serve as potential mediators. Two-sample Mendelian randomization analysis was applied to infer causality using Inverse Variance Weighted (IVW), MR Egger, weighted media, simple mode and weighted mode method. Subsequently, sensitivity analysis was conducted to ensure the robustness of the MR results. In addition, we conducted reverse MR analysis to alleviate reverse causality. Finally, we used mediation analysis to determine the pathway mediated by inflammation-related proteins from the gut microbiota to OL.ResultsThe five bacterial taxa in the gut microbiota indicate a potential causal relationship with the development of OL. Notably, family Clostridiaceae1 was negatively correlated with the risk of OL development, while genus Dorea, genus Ruminococcus1, genus Senegalimasilia and genus Veillonella were positively associated with the risk of OL development. In addition, this study identified a potential causal relationship between interleukin-10 receptor subunit alpha (IL-10RA), interleukin-18 receptor 1(IL18-R1) and the occurrence of OL. In addition, intermediary analysis indicates that IL18-R1 mediated the pathway between the gut microbiota genus Senegalimasilia and OL.ConclusionsIn summary, our research emphasize the complex relationship between gut microbiota, inflammation-related proteins and OL. The identified associations and mediating effects provide new insights into potential therapeutic approaches for targeting the gut microbiota in the management of OL, and contribute to its prevention, diagnosis and treatment.